ANALYSIS OF THE COMPETITIVE ADVANTAGE SUSTAINABILITY FACTORS BASED ON THE KEY COMPETENCIES OF AN ELECTRICAL ENGINEERING ENTERPRISE - S. B. Moiseev (Вестник университета)
The factors influencing the possibility of the theory of key competencies adaptation within the traditional ideas of the resource approach to ensure the long-term competitiveness of companies have been considered. For this purpose, the review of features of application of key competencies during the formation of strategies of the industrial companies of mature sectors of industries has been carried out, in which thanks to action of evolutionary mechanisms of technological and organizational development there are objective preconditions for creation of steady competitive advantages on their basis. The necessity of development of methodological approaches to the formation of company’s competitive strategy in the sector of electrical production based on the formation of organizational-economic mechanism of adaptation to external influences and internal changes to manage the development of key competencies as factors of sustainable competitive advantage in the future and the formation of long-term effective business development model of the enterprise, has been substantiated.